Tainna = The unseen ones : short stories - Dunning, Norma (Douglas & McIntyre, 2021)
"Drawing on both lived experience and cultural memory, Norma Dunning brings together six powerful new short stories centred on modern-day Inuk characters in Tainna. Ranging from homeless to extravagantly wealthy, from spiritual to jaded, young to elderly, and even from alive to deceased, Dunning's characters are united by shared feelings of alienation, displacement and loneliness resulting from their experiences in southern Canada. In Tainna--meaning 'the unseen ones' and pronounced Da e nn a--a fraught reunion between sisters Sila and Amak ends in an uneasy understanding. From the spirit realm, Chevy Bass watches over his imperilled grandson, Kunak. And in the title story, the broken-hearted Bunny wanders onto a golf course on a freezing night, when a flock of geese stand vigil until her body is discovered by a kind stranger. Norma Dunning's masterful storytelling uses humour and incisive detail to create compelling characters who discover themselves in a hostile land where prejudice, misogyny and inequity are most often found hidden in plain sight. There, they must rely on their wits, artistic talent, senses of humour and spirituality for survival; and there, too, they find solace in shining moments of reconnection with their families and communities."--